A Case of Atraumatic Splenic Rupture in Twin Pregnancy - Sivaslıoğlu, Akın; Demir, Berfu; Gelişen, Orhan; Dilbaz, Serdar; Şahin, Yılmaz; Dölen, İsmail (Gynecology Obstetrics & Reproductive Medicine, 2006)
A 31 year old woman with 34 weeks of twin pregnancy underwent caserean section for fetal distres. Before the uterine incision, hemoperitoneum was observed and splenic rupture was detected when the origin of the bleeding was sought and primary repair was performed using compression sutures. As splenic rupture is a rare complication that is encountered during pregnancy, there might be a delay in diagnosis but emergency intervention is essential as haemorrhagic shock can easily develop in a short time.